Sounds in the scenes: a debate on the theme (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
This debate took place on October 30, 2021 as a public call for the thematic dossier with the same title. It is hosted on the YouTube platform on the Luz Laboratório UDESC channel, belonging to the Lighting Laboratory of the State University of Santa Catarina. The debate was part of the program for the tenth edition of the A Luz em Cena event. The members of the editorial commission of the Fourth Dossier included Flora Holderbaum, Thais Oliveira, Morgana Martins, Ernani Maleta and José Claudio Castanheira as debaters. The opening and closing was coordinated by Marcelo Araújo as a representative of the event.
Keywords: Debate; Sounds in Scenes; Event A Luz em Cena